2017
DOI: 10.5858/arpa.2016-0222-oa
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Automated Impedance and Optical Fluorescence Platelet Counts Compared With International Reference Method in Patients With Thalassemia

Abstract: - Among the evaluated methods, PLT-I was the method least correlated to IRM, with PLT-O and PLT-F comparable to IRM in patients with thalassemia. Optical platelet counts and careful blood smear examination are recommended alternative platelet counting methods, depending on the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
3
23
1
Order By: Relevance
“…For instance, Tantanate et al used samples from thalassemia patients, but we did not restrict to a specific disease population. Furthermore, Tantanate et al [7] found that optical methods were more consistent with the reference method IRM than impedance methods for counting platelets at normal levels, which was also inconsistent with our results. Our results demonstrated that in normal platelet levels, the consistency of the impedance method was higher than the optical method, whether in a Sysmex XN-9000 instrument or a BC-6000 Plus instrument.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…For instance, Tantanate et al used samples from thalassemia patients, but we did not restrict to a specific disease population. Furthermore, Tantanate et al [7] found that optical methods were more consistent with the reference method IRM than impedance methods for counting platelets at normal levels, which was also inconsistent with our results. Our results demonstrated that in normal platelet levels, the consistency of the impedance method was higher than the optical method, whether in a Sysmex XN-9000 instrument or a BC-6000 Plus instrument.…”
Section: Discussioncontrasting
confidence: 99%
“…All evaluated methods had acceptable sensitivity, specificity, and coincidence rates for the diagnosis of thrombocytopenia and thrombocytosis, which was consistent with the findings of Tantanate et al [7]. Thus, all assessed methods can be used for screening and exclusion of patients with thrombocytopenia and thrombocytosis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Now the impedance platelet count is widely used in many clinical laboratories for routine patient testing [13][14][15][16]. However, the use of both impedance and optical This study confirmed that PLT-F on XN-9000 is a preferred method for low platelet counting especially the hemolyzed samples.…”
Section: The Qc Results Of Plt-i and Plt-f System At Low Platelet Coumentioning
confidence: 51%